Kontribusi Tradisi Lokal Orang Tua Terhadap Pembentukan Karakter Disiplin pada Siswa SMA Negeri Mutis Eban, NTT - Salu, Aqualina; Hunam, Damianus; Tael, Elfiana (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This study aims to identify the contribution of local parental traditions to the formation of discipline character in students at SMA Negeri Mutis Eban, NTT. Discipline character is an essential aspect of students' personal development, influencing their academic and social success. This research employs a qualitative approach with a case study method to explore the role of local traditions in fostering discipline among students. Data were collected through interviews with parents, teachers, and students, as well as observations of daily activities related to local traditions in the Eban community. The findings indicate that daily activities such as working together, participation in traditional ceremonies, and parental role modeling significantly contribute to students' discipline. Parents who set a good example in their daily lives and instill responsibilities in their children have a profound impact on the students' discipline at school. Moreover, community activities like gotong royong and traditional ceremonies, which emphasize values of togetherness and orderliness, further reinforce the discipline character in students. These findings suggest that education based on local traditions can serve as an effective alternative in nurturing children's discipline, highlighting the crucial role of families and communities in the learning process. This study is expected to provide new insights into the importance of integrating local traditions in character education in Indonesia.